Thrombophilia and inflammatory bowel disease: does factor V mutation have a role? - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 1998)
Background An increased tendency for thromboembolism is a well known problem of inflammatory bowel disease (IBD). Microvascular thrombosis has also been claimed as a pathogenic factor in IBD. Recently a point mutation in the gene coding factor V (FV Leiden) has been identified in various thromboembolic diseases, but the role in IBD is unknown. Objective To determine the frequency of FV Leiden in IBD patients and compare with a group of controls. Methods Sixty-three IBD patients [43 ulcerative colitis (UC) patients and 20 Crohn's disease (CD) patients] and 36 healthy controls were included in the study. Only one of the UC patients had a history of cerebral thromboembolism. The extracted DNA from frozen blood was subjected to polymerase chain reaction for the amplification of FV gene. The amplicons were hybridized both with the mutant and wild-type probes to detect FV mutation. Readings of optical density above 0.3 were considered as positive results. According to the patterns of ELISA, heterozygosity and homozygosity for normal and mutant alleles were determined. Results Eight (18%) of UC patients were heterozygous normal and one (2%) patient had homozygous mutation. Eight (45%) of the 20 CD patients had a heterozygous pattern and one (5%) had a homozygous pattern. In the control group four (11%) subjects showed a heterozygous genotype. FV Leiden was found to be statistically more frequent in CD patients (P < 0.005) (odds ratio 6.5, 95% confidence interval 1.3-18.), but not in the UC patients as compared with controls (P > 0.05). There was no significant correlation between FV Leiden presence and disease activity, gender or disease duration for both UC and CD. Conclusion The results suggest that FV Leiden is more frequent in CD patients, but not in the UC patients as compared with controls. The high rate of factor V mutation in our CD patients suggests the need for further studies to confirm a relationship between this mutation and aetiology of the disease. fur J Gastroenterol Hepatol 10:827-829 (C) 1998 Lippincott Williams & Wilkins.
Keywords: ulcerative colitis; Crohn's disease; thrombophilia; FV Leiden; activated protein C resistance; ACTIVATED PROTEIN-C; COAGULATION-FACTOR-V; CROHNS-DISEASE; VENOUS THROMBOSIS; BLOOD-COAGULATION; THROMBOEMBOLISM; RESISTANCE; INFARCTION; LEIDEN